Employment Effects of Outsourcing to Low Wage Countries. Empirical Evidence for EU Countries - Martin Falk; Yvonne Wolfmayr (Austrian Institute of Economic Research (WIFO), 2005)
This paper investigates the impact of international outsourcing on total employment using two-digit manufacturing data for seven EU countries for the period of 1995-2000. As is common in other empirical work, international outsourcing is measured as imports in intermediate imports. Estimates using OLS first differences show that imported materials from the same industry originating from low-wage countries have a significant and negative impact on total employment. The estimates suggest that rising intermediate imports from low-wage countries may account for an approximate reduction of 0.25 percentage points in employment per year. Sample split regressions show that the impact of imported materials from low-wage countries is statistically significant in industries with low skill intensity but not in skill intensive industries such as machinery, electrical, optical and transport equipment.
Keywords: F10; J31; 330; Trade in intermediate imports; labour demand; cross-country analysis; Outsourcing; Niedriglohn; Beschäftigungseffekt; Schätzung; EU-Staaten